Conceptions and (Mis)conceptions of Science in International Treaties; the ICJ Whaling Case in Context - Brendan Gogarty (2015)
The recent judgment in the International Court of Justice case Whaling in the Antarctic (Australia v. Japan: New Zealand intervening) determined that Japanese ‘special permit’ whaling in the Southern Ocean was not ‘for the purposes of scientific research’. This is the only exemption permitted under the International Convention for the Regulation of Whaling’s current moratorium on commercial whaling. The Court made its determination by characterising the Japanese research program as a scientific program, but failing to define what scientific research actually was or was not. This paper presents the background to the decision, and challenges the reasoning of the Court and its standard of review test. It concludes that the Court failed to take the opportunity to offer a clear determination to states on their legal–scientific obligations within international law.